“Optimización de la eficiencia productiva del proceso “ELPO” mediante estudios de tiempos en la empresa CIAUTO”. - Arequipa Punina, Cristian Bladimir (2024)
The project degree is focused on improving the productive efficiency of the "ELPO" process in the CIAUTO company through the implementation of time studies. The need to carry out a detailed study of times and movements has been raised in order to identify and emphasized bottlenecks situation that are affecting productivity in the process. The research is justified by its ability to develop engineering standards based on acceptable business practices and the average times required to perform repetitive tasks within the enterprise. A mixed methodology was used that has been integrated qualitative and quantitative methods, evaluating the operational efficiency and its costs. It is expected, this study implementation will allow adequate planning of production in the CIAUTO company in a best form, thus contributing a significant improvement in the efficiency and productivity of "ELPO" process. Furthermore, it is expected that this approach will have a positive impact on the development and training of staff, by providing them tools and knowledge that allow performing their duties efficiently and effectively.